PENNSYLVANIAN CONODONTS AND MICROFACIES FROM NORTHEASTERN MEXICO (TAMATÁN GROUP, CIUDAD VICTORIA BLOCK) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
The biostratigraphic analysis of the Paleozoic sedimentary successions in Mexico is crucial for understanding their age, depositional setting, and paleogeographic implications. This study examined conodonts and microfacies of calcareous strata within the Del Monte Formation of the Tamatán Group in northeastern Mexico.Field observations have led to the identification of three units within the Del Monte Formation: Unit 1, characterized by calcareous sandstone, bioclastic limestone, shale, occasional conglomerate, and dolomitized beds; Unit 2, consisting of conglomerate and/or breccia associated with debris flows; and Unit 3 including turbiditic sandstone and shale.Conodonts were only recognized in Unit 1, with such genera as Idiognathoides, Neognathodus, Idiognathodus and less frequently, Streptognathodus, Adetognathus, and Diplognathodus. The faunal associations include Idiognathoides cf. Id. corrugatus Harris & Hollingsworth, 1933, Idiognathoides sulcatus sulcatus Higgins & Bouckaert, 1968, Idiognathoides convexus (Ellison & Graves, 1941), Idiognathoides asiaticus Nigmadganov & Nemyrovskaya, 1992, Neognathodus cf. N. atokaensis Grayson, 1984, Neognathodus aff. bothrops Merrill, 1972, Neognathodus nataliae Alekseev & Gerelzezeg, 2001 (in Alekseev & Goreva 2001), Streptognathodus parvus Dunn, 1966, Idiognathodus incurvus Dunn, 1966, and Idiognathodus aff. delicatus Gunnell, 1931, suggesting Morrowan and Atokan (Pennsylvanian) ages for the dolomitic limestone and grainstone beds.Five types of microfacies (MF) and several marine facies zone (FZ) have been detected: MF1-bioclastic grainstone and MF2-wackestone deposited at the platform margin (FZ 6 and FZ 7), MF3-dolomitized wackestone representing an inner restricted platform (FZ 8), MF4-mudstone from a deeper water zone (FZ 4), and MF5-siliciclastic beds with bioclasts indicating a high-energy barrier associated with a platform margin (FZ 6). The findings confirm a shallow to deep platform and imply a connection among Mexican peri-Gondwanan basins, including the Tamatán Basin, indicating similarities in sedimentary facies and/or depositional environments linked to the Rheic Ocean during the Early to Middle Pennsylvanian.
Keywords: Biostratigraphy; Morrowan-Atokan; Depositional environments; Del Monte Formation; Peri-Gondwanan Basin